Word Stress of Derive word - Muammar Suharso; Silvi Angelika; Yani Lubis (Jurnal Pendidikan dan Sastra Inggris, 2023)
Due to the fact that pronunciation is a fundamental component of English conversations, it is crucial that it be done correctly. word stress of derived words is one of the important aspects of English pronunciation that affects the understanding and expression of word meanings accurately. The goal of this study is to examine the word stress patterns in words that are English-derived. Although there are variations and exceptions, word stress in derived words typically adheres to a set of rules and patterns. In this study, we examine the word stress patterns in noun to verb, adjective to noun, and verb to noun derivations. Additionally, we looked at how prefixes and suffixes affected stress patterns. The purpose of this study is to advance the field of English pronunciation and provide a better understanding of the stress patterns in derived words. In this study, we collected data and examined stress patterns using a variety of sources, including dictionaries and pronunciation guides. The findings of this study can aid English language learners in getting better at pronouncing words. The findings of this study might help English learners in perfecting their pronunciation abilities and understanding words derived from them more precisely.